Untreated Celiac Disease in a Patient with Dermatitis Herpetiformis Leading to a Small Bowel Carcinoma - Monique H.M. Derikx; Tanya M. Bisseling (Case Reports in Gastroenterology, 2012)
Usually, celiac disease has a benign course, though the overall morbidity and mortality have increased. Treatment with a gluten-free diet restores the damaged intestinal mucosa. In rare cases a small bowel adenocarcinoma develops. Unfortunately, the clinical presentation is not always recognized and prognosis is bad. We present a 69-year-old man with a history of dermatitis herpetiformis who presented to our tertiary center for a second opinion for a suspected gastric motility disorder. This diagnosis was based on the combination of upper abdominal pain for over 2 years and repetitive episodes of vomiting. Immediately after referral, celiac disease was diagnosed and a gluten-free diet was started. In the next half year of follow-up, additional anemia and weight loss developed and eventually a small bowel adenocarcinoma was diagnosed. Revision of a small bowel follow-through, which had been performed 2 years earlier, showed that the tube had been positioned just distal from the process. Therefore, this diagnosis had not been made at that time. Unfortunately, curative therapy was not possible and the patient died a few months later. In conclusion, all patients with dermatitis herpetiformis have a gluten-sensitive enteropathy and should be treated with a gluten-free diet. Next to this it is important to notice that patients with celiac disease have an increased risk of developing a small bowel malignancy. Unexplained upper abdominal pain, weight loss and anemia should lead to additional investigations to exclude a small bowel malignancy in these patients. At last, the diagnosis of a small bowel carcinoma is difficult. Together with the radiologist, the optimal techniques for visualization of this malignancy should be considered.